Engaging Youth Worldviews in Africa: A Practical Theology in Light of John 4 - Ndereba, Kevin Muriithi (Conspectus: The Journal of the South African Theological Seminary, 2021)
This essay problematizes worldview engagement in Africa from a Kenyan context. The author suggests that robust youth engagement must straddle the traditional/animistic, modern, atheistic, and postmodern worldviews. The essay approaches the study using a practical theological methodology, which deepens the interplay of theory and praxis. In particular, the essay is grounded in Osmer's approach which asks four questions. The first question is the descriptive-empirical question, “what is happening,” that explores the state of African youth ministry; the second question is the interpretive question, “why is this happening,” which unpacks worldview issues in the lives of young people; the third question is the normative question, “what ought to be happening,” and will engage Johannine Christology in John 4. The fourth question is the pragmatic question, which asks, “how can we apply this,” and offers recommendations for youth ministry practice and higher education.
free
Keywords: Apologetics; Johannine Christology; Practical theology; Worldviews; Youth ministry